Study on Critical Hydraulic Gradient Theory of Flow Soil Failure in Cohesive Soil Foundation. (2nd June 2021) - Zhou, Mei; Dang, Faning; Li, Yutao; Ding, Jiulong; Gao, Jun
Abstract : The current formula of critical hydraulic gradient is not adapted to solve critical hydraulic gradient of cohesive soil. Assume that the seepage failure mode of the cohesive soil foundation was cylindrical or inverted circular truncated cone, based on the calculation formula of the critical hydraulic gradient of Terzaghi, the analytical formula of the critical hydraulic gradient considering the influence of the shear strength of the soil was derived. Then, the seepage failure process of the clay layer was simulated numerically, and the effects of the clay layer thickness, failure radius, and shear strength indexes on the critical hydraulic slope were analyzed. The comparison results show that the numerical test results are in good agreement with the calculated results of the new formula. In addition, the critical hydraulic gradient of sandy loam and loess under different working conditions was studied severally by a self-made permeation failure instrument. The results show that the critical hydraulic gradient decreases with the increase of soil thickness and failure radius, and the maximum error between the test and the corresponding formula results is no more than 16%.